Pengalokasian Dana Bulanan Mahasiswa secara Optimal Menggunakan Metode Big-M - Nabila Rizki Aprilia; Siti Salamah Br Ginting; Pinkan Indriani Daulay; Fadhil Abdullah (CV. KAMPUS AKADEMIK PUBLISING, 2025)
Proper monthly budget management is often a challenge for students, especially when they have to meet basic needs with limited resources. This study aims to improve monthly fund allocation for students through the use of the Big-M method in linear programming. A mathematical model is developed based on the priority of needs and limited budget, considering constraints in the form of inequalities (≥) that require surplus variables and additional variables. The Big-M method is applied in a simplex approach by giving a large penalty (M) to the additional variables to achieve an optimal solution. The findings of the study indicate that this method is effective in providing a balanced and efficient fund allocation between primary needs such as food and education, and also additional needs such as transportation and entertainment. Therefore, the Big-M method can be used as a logical and structured tool in student financial planning.